A new species of Atriplex (Amaranthaceae) from the Indian subcontinent - Sukhorukov, Alexander P.; Singh, Nidhan; Kushunina, Maria A.; Zaika, Maxim A.; Sennikov, Alexander N. (PhytoKeys)
A new subshrubby C4 -species from the lowlands and foothills of India, Pakistan and SE Afghanistan, Atriplex pseudotatarica, is described and illustrated. Previously, it was incorrectly identified as A. crassifolia auct. non C.A.Mey. belonging to a distant C3 -group of the genus. A phylogenetic analysis based on nrITS and nrETS revealed its position as sister to A. schugnanica (sect. Obionopsis). Both species share aphyllous inflorescence and smooth bract-like cover, but differ in life form, leaves, seed colour, and geographical distribution. We revised native Indian Atriplex species and excluded some of them from the flora of the country. An improved checklist of the native Atriplex species in India with their corrected synonymy and nomenclature is given, and a new diagnostic key is provided.